Selection of S18326 as a New Potent and Selective Boronic Acid Direct Thrombin Inhibitor - Rupin, A; Mennecier, P; Lila, C; de Nanteuil, G; Verbeuren, T J (Thrombosis and Haemostasis, 1997)
Using enzymatic microassays, the potency of a series of new boroarginine tripeptides was determined versus thrombin and a panel of serine-proteases implicated in the coagulation and fibrinolysis pathways. The inhibition of the serine-protease complement factor I was also studied. Factor I regulates the alternate pathway of the complement and its inhibition appears to be responsible for the toxic effects of the orally available thrombin inhibitor Ac-D-Phe-Pro-boro-Arg (DuP-714). The structure of the new boronic acid derivatives tested was modified from that of DuP-714 by replacing the proline in the P2 position by N-cycloalkyl-glycine residues of increasing size (SI8989: cyclopropyl; S18563: cyclobutyl; S18326: cyclopentyl; S18229: cyclohexyl). All compounds were found to be slow-tight binding inhibitors of thrombin versus purified human fibrinogen. Replacement of proline by N-cycloalkyl-glycines did not decrease the anti-thrombin potency of the substances up to the cyclopentyl size and this result was confirmed by classical coagulation assays with human plasma in vitro. In contrast, the inhibitory activities of the four new boronic acids were found to be lower than those of DuP-714 versus plasmin, urokinase (u-PA), plasmatic kallikrein, activated protein C (aPC) and complement factor I. The cyclopentyl derivative SI8326 is a slightly more active inhibitor of thrombin than DuP-714 (initial IC50 values 3.99 ± 0.18 nM versus 4.73 ± 0.27 nM, respectively). Moreover SI8326 was identified as the most selective compound of the series with relative potencies being 2 to 29 fold higher than that of DuP-714 versus the panel of serine-proteases tested; the rank order of potency versus the other serine-proteases for S18326 was t-PA>kallikrein>aPC> factor I>plasmin>fXa>u-PA. These results indicate that the size of the thrombin hydrophobic pocket S2 is sufficient to accept larger residues than proline in the P2 position of Ac-D-Phe-X-boroArg derivatives while this is not the case for other important serine-proteases of the fibrinolysis, coagulation and complement pathways. The N-cyclopentyl glycine containing derivative SI8326, which is the most potent and the most selective anti-thrombin compound of the series, currently undergoes major preclinical testing.